2004
DOI: 10.1097/01.hjh.0000133734.32125.c7
|View full text |Cite
|
Sign up to set email alerts
|

Red wine polyphenols prevent cardiovascular alterations in L-NAME-induced hypertension

Abstract: Our results provide evidence that Provinols partially prevents L-NAME-induced hypertension, cardiovascular remodeling and vascular dysfunction via the increase of NO-synthase activity and prevention of oxidative stress. Thus, the beneficial effects of plant polyphenols in prevention of hypertension may result from their complex influence on the NO balance in the cardiovascular system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
67
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(76 citation statements)
references
References 32 publications
9
67
0
Order By: Relevance
“…In addition, we showed that refreshed endothelium-dependent vasorelaxation was accompanied by the increased activity of NO-synthase in the left ventricle after the treatment with Provinols TM . Our results are in a good consensus with observations in the model of NO-deficient hypertension where the potentiation of the inhibited thoracic aorta vasorelaxation has been attributed to the activation of NO pathway by polyphenols (Bernátová et al 2002;Pecháňová et al 2004). Moreover, the increased production of NO due to stimulation of NO-synthase activity in arterial wall (also in aorta) due to the action of polyphenolic compounds has been confirmed by observations of our as well as other laboratories (Stocklet et al 1999;Zenebe et al 2001;Benito et al 2002).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In addition, we showed that refreshed endothelium-dependent vasorelaxation was accompanied by the increased activity of NO-synthase in the left ventricle after the treatment with Provinols TM . Our results are in a good consensus with observations in the model of NO-deficient hypertension where the potentiation of the inhibited thoracic aorta vasorelaxation has been attributed to the activation of NO pathway by polyphenols (Bernátová et al 2002;Pecháňová et al 2004). Moreover, the increased production of NO due to stimulation of NO-synthase activity in arterial wall (also in aorta) due to the action of polyphenolic compounds has been confirmed by observations of our as well as other laboratories (Stocklet et al 1999;Zenebe et al 2001;Benito et al 2002).…”
Section: Discussionsupporting
confidence: 79%
“…Our previous experiments using the model of experimental hypertension demonstrated protective effects of red wine polyphenols on increased blood pressure, myocardial fibrosis, vascular wall remodeling and impaired arterial reactivity. Improved vascular function and structure in this model was associated with reduced oxidant status as well as with the increased NO production after activation of NOsynthase (Bernátová et al 2002;Pecháňová et al 2004).…”
Section: Introductionmentioning
confidence: 92%
“…The decreased eNOS protein expression in this study is likely due to the down-regulation of eNOS gene expression. On the other hand, other report showed that L-NAME induced an increased eNOS mRNA expression but that aortic NOS activity was, in fact, decreased (Pechanova et al 2004). It still could not readily explain the discrepancy of the levels of mRNA expression found in L-NAME-treated rats.…”
Section: Discussionmentioning
confidence: 70%
“…Rats were then divided randomly in six experimental groups as follows: the first group (n = 6) served as control and received tap water only. In the second group (L-NAME group, n = 6), L-NAME was added to drinking water at a concentration of 0.4 mg/ml to account for a daily intake of 40 mg/kg (Bernàtovà et al, 2002;Pechanova et al, 2004;Jendekova et al, 2006;Javorkova et al, 2007). The third group (AuL group, n = 8) received simultaneously L-NAME (40 mg/kg/day) and AuL extract at 250 mg/kg/day (Ziyyat and Boussairi, 1998).…”
Section: Model Of L-name-induced Arterial Hypertension and Experimentmentioning
confidence: 99%
“…The polyphenolic compounds have beneficial properties for preventing cardiovascular alterations in nitric oxide (NO) deficient hypertension (Bernàtovà et al, 2002;Pechanova et al, 2004;Curin and Andriantsitohaina, 2005;Perez-Vizcaino et al, 2006). This is the reason for our choice of the N Gnitro-l-arginine methyl-ester (L-NAME) experimental model of hypertension characterized by pronounced target organ damages.…”
Section: Introductionmentioning
confidence: 98%